2014
DOI: 10.5812/hepatmon.25792
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization Therapy for Patients With Unresectable Hepatocellular Carcinoma

Abstract: Background:Although transcatheter arterial chemoembolization (TACE) has been widely used as a palliative treatment for unresectable hepatocellular carcinoma (HCC), its actual efficacy and prognostic usefulness have not been clarified in past studies.Objectives:The aim of the study is to investigate the efficacy, complications, and prognostic factors of the TACE in unresectable HCC patients.Patients and Methods:Thirty-two patients with unresectable HCC were treated with TACE. The procedure was performed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Our previous studies have found that, the injury and rupture of small artery in liver tissue may relate to the bleeding complication (14)(15)(16)(17). With the embolization agents, TAE can block small artery (18,19), achieving dual effects of haemostasis and delaying tumor growth. Therefore, the same prognosis is present in RHCC and NHCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have found that, the injury and rupture of small artery in liver tissue may relate to the bleeding complication (14)(15)(16)(17). With the embolization agents, TAE can block small artery (18,19), achieving dual effects of haemostasis and delaying tumor growth. Therefore, the same prognosis is present in RHCC and NHCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple variables affect the clinical course of HCC, [ 11 ] the number of studies comparing TACE to conservative management remains limited. [ 12 , 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…The majority of adverse events, however, were in the realm of post-embolization syndrome. Furthermore, elevations of ALT or AST occurred with significant frequency within 48 h after dTACE, albeit with no significant change in liver toxicity compared with pre-dTACE within 2 months (as with cTACE) (35).…”
Section: Discussionmentioning
confidence: 88%